Peningkatan Kemampuan Membaca Permulaan Pada Kelompok B Melalui Media Kartu Kata Bergambar - Tuti Sri Wahyuni; Gunawan Gunawan; Baik Nilawati Astini; Ika Rachmayani (Indonesian Publication Center, 2023)
Early reading in early childhood is very important because it affects the improvement of reading skills in the future. The purpose of this study was to improve the initial reading ability of group B through the media of picture word cards. This classroom action research using Kurt Lewin's model was conducted in two cycles. The subjects in this study were 12 children in group B in Al-Mulk Islamic Kindergarten consisting of 4 boys and 8 girls. Data collection techniques in this study are observation and documentation. The research instrument used was an observation sheet in the form of a checklist. The indicator of success in this study is if the child experiences an increase in initial reading ability using picture word card media by 75% or with developing criteria as expected. The results of the study showed that the average value of each cycle increased. So it can be concluded that the initial reading ability of group B can be improved through the use of picture word cards.